The application of a CAL strategy in science and mathematics for disadvantaged Grade 12 learners in South Africa - Hartley, M.; Treagust, David; Ogunniyi, M. (Elsevier, 2008)
This study addressed one aspect of a national strategic recommendation in South Africa by examining the effectiveness of computer-based outreach programmes in terms of how the programmes were implemented and learners' perceptions of the classes. The role that the computer centres played at two schools was examined and the research endeavoured to provide descriptions of the implemented and perceived programmes. The findings provide insight into the implementation of computer-assisted learning (CAL) in disadvantaged schools and serve as baseline data for research into CAL environments in the South African context. Learners considered the application of CAL as a positive step to improve their learning but also placed a high value on the role of the teacher because of the perceived competencies of their teachers in helping them perform well in the matriculation examination. The findings of the study have important practice and policy implications for the implementation of CAL in disadvantaged schools. © 2007 Elsevier Ltd. All rights reserved.